Switched Optimized Robust Control of Uncertain LPV Systems Subject to Structural Faults - Buzachero, Luiz F.S.; Assunção, Edvaldo [UNESP]; Teixeira, Marcelo C.M. [UNESP]; da Silva, Emerson R.P. (Elsevier, 2018)
This paper proposes improved techniques for the control of continuous-time, switched uncertain linear LPV systems with decay rate performance index and optimization of the controller's norm. These techniques are of closed loop nature (trajectory dependent) and are designed using the solution of Lyapunov-Metzler inequalities from which the stability condition is expressed. The performance index used in the design procedure is the decay rate that aims to reduce the system's settling time. The other important tool proposed is the optimization of the controller's norm that aims to reduce the gains and facilitate its application. In addition to this, more relaxed conditions than those existing in the literature to obtain switched controllers are proposed, which will enable better global performance. Practical implementation of the improved techniques were made in a Quanser's Active Mass Damper - One Floor (AMD-1) laboratory prototype, subject to a structural failure, addressed as a polytopic time-varying uncertainty.
Keywords: Fault Tolerant Control; Hybrid; Performance; Robust Stability; Switched Systems